Contested Urban Space: Informal Parking Practices and Urban Marginalization in Makassar City - Ahmad, M. Ridwan Said; Puspita, Nurfadila; Fhath, Muhammad; JT, Aulya Ramadhani (Citra Media Publishing, 2025)
Studies on illegal parking and the dynamics of urban spatial planning have generally been written within the framework of a structural perspective that views the phenomenon of illegal parking solely as a form of violation of order, law, and formal spatial planning. This approach often ignores the social dimensions that underlie the emergence of this practice, as well as how marginalized groups try to survive amidst limited access to urban space and resources. This article attempts to offer an alternative perspective by discussing the dynamics of urban space that is contested through illegal parking practices in Makassar City. This research was conducted on the phenomenon of illegal parking in the Panakukang Mall area, one of the largest modern shopping centers in the city. The research findings show that illegal parking practices are a form of informal use of public space that reflects power relations and social inequality in the urban context. Illegal parking perpetrators develop various survival and adaptation strategies, as well as community solidarity, in response to economic pressures and unfair regulations. Illegal parking in this area is a real reflection of urban marginality, where marginalized groups try to maintain their existence in an increasingly exclusive city landscape dominated by the logic of formality and commercialization. This article highlights the importance of reading urban space not only as a physical entity, but also as an arena for struggles over access, legitimacy, and the survival of marginalized groups.